The Use of Economics in International Trade and Investment Disputes - Carpenter, Theresa (Cambridge University Press, 2017)
Containing contributions from both academic experts and practitioners and from economic and legal experts, this book explores the use of economics in international economic law
Description based on publisher supplied metadata and other sources
Keywords: World Trade Organization; International commercial arbitration; Internationales Handelsrecht; Internationale Handelsschiedsgerichtsbarkeit; Aufsatzsammlung